UZBEKISTAN'S NEW CONSTITUTION – LEGAL GUARANTEE OF PUBLIC SAFETY (Academicia Globe: Inderscience Research, 2024)
In this article, the author analyzed the standards for the maintenance of public safety strengthened in the new edition of the Constitution of the Republic of Uzbekistan, as well as revealed the importance of the Constitution as a legal basis for public safety. He also highlighted the activities of the Situational and Analytical Center, which was established to improve the system of public safety.